Lipid lowering drug therapy in patients with coronary heart disease from 24 European countries – Findings from the EUROASPIRE IV survey. (March 2016) - Reiner, Ž.; De Backer, G.; Fras, Z.; Kotseva, K.; Tokgözoglu, L.; Wood, D.; De Bacquer, D.; ,
Abstract: Objective: Since dyslipidaemia is one of the most important risk factors for coronary heart disease (CHD), lowering of LDL-cholesterol (LDL-C) causes significant reduction in morbidity and mortality, particularly in patients with established CHD. The aim of this survey was to assess how statins were prescribed in CHD patients at discharge after a coronary event from hospitals throughout Europe and how the intake of these drugs was reported by the patients when they were seen more than one year later in relationship with their achieved LDL-C levels. Methods: 6648 CHD patients' data from centres in 24 European countries were gathered using standardized methods. Lipid measurements were performed in one central laboratory. Patients were divided in three groups: high-intensity statin therapy, moderate or low intensity statin therapy and no statin therapy at all. Results: 90.4% CHD patients were on statin therapy at the time of discharge from the hospital which decreased to 86% one year later. Only 37.6% of these patients were prescribed a high-intensity statin at discharge which even decreased to 32.7% later. In only 6 countries (all of them high-income countries) the number of patients on a high-intensity statin therapy increased substantially after the hospital discharge. It is worrying that statin therapy was discontinued in 11.6% and that only 19.3% of all CHD patients achieved target values of LDL-C < 1.8 mmol/L at the time of interview. Conclusions: Too many CHD patients with dyslipidaemia are still inadequately treated and most of these patients on statin therapy are not achieving the treatment targets. Therapeutic control of LDL-C is clearly related to the intensity of lipid lowering drug regimen after the CHD event indicating that a considerable potential still exists throughout Europe to reduce CHD mortality and morbidity rates through more efficient LDL-C lowering. Highlights: Management of dyslipidaemia in CHD patients in Europe has improved over the last ten years. A large majority of CHD patients with dyslipidaemia is still inadequately treated. Many CHD patients on lipid-lowering therapy are not reaching the treatment goals for lipids according to the guidelines. A potential exists throughout Europe to reduce CHD mortality and morbidity rates through better treatment of dyslipidaemia.